Study of PEG-rhG-CSF for the prevention of neutropenia in concurrent chemoradiotherapy for nasopharyngeal carcinoma - Lu Yang; Lei Yu; Xue Du; Yu Cui; Guobo Du (PLoS ONE, 2025)
Background To study the efficacy and safety of Polyethylene glycolated recombinant human granulocyte colony-stimulating factor (PEG-rhG-CSF) in the prevention of neutropenia during concurrent chemoradiotherapy for nasopharyngeal carcinoma (NPC). Methods This is a single-center, prospective, randomized controlled study conducted from June 1, 2021, to October 31, 2022 on patients diagnosed with locally advanced NPC. Participants were divided into an experimental group and a control group. The experimental group received PEG-rhG-CSF injections post-chemotherapy cycles, whereas the control group received standard care without additional intervention. Outcomes assessed included grade 3/4 neutropenia incidence, blood cell count changes, febrile neutropenia rates, delays or interruptions in chemotherapy/radiotherapy due to hematological toxicity, oral mucositis incidents, and bone pain occurrences, comparing these between both groups. Results 1. 88 patients with locally advanced NPC were included, the incidence of grade 3 neutropenia in the experimental group was lower than that in the control group (P = 0.026); 2. The white blood cell count and neutrophil count in D7, D10, D14, and D21 in the experimental group were higher than those in the control group (P<0.01); 3. The rate of delayed chemotherapy in the experimental group was lower than that in the control group (2.3% vs. 29.5%), P = 0.001; the rate of interruption of radiotherapy in the experimental group was lower than that in the control group (2.3% vs.27.3%), P = 0.003; 4. The incidence of bone pain in the experimental group was 34.1%, of which most were mild bone pain, and no severe bone pain occurred. The leukocyte and neutrophil counts of the patients in the bone pain group were significantly higher than those of the patients in the no bone pain group, P(WBC) = 0.001, P(ANC) = 0.002. Conclusions The preventive use of PEG-rhG-CSF decreases the incidence of neutropenia in patients undergoing concurrent chemoradiotherapy for NPC, thereby reducing rates of chemotherapy delays and radiotherapy interruptions, with mild adverse reactions that are tolerable by patients.